2013
DOI: 10.5194/essdd-6-163-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global database of surface ocean particulate organic carbon export fluxes diagnosed from the <sup>234</sup>Th technique

Abstract: Abstract. The oceanic biological carbon pump is an important factor in the global carbon cycle. Organic carbon is exported from the surface ocean mainly in the form of settling particles derived from plankton production in the upper layers of the ocean. The large variability in current estimates of the global strength of the biological carbon pump emphasises that our knowledge of a major planetary carbon flux remains poorly constrained. We present a database of 723 estimates of organic carbon export from the s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 81 publications
2
29
1
Order By: Relevance
“…(2013) dataset may include more studies from diatom-rich ecosystems with high POC: 234 Th organic particles, such as observed by (Buesseler, 1998; not included in Le Moigne et al 2013), driving some of the discrepancy between our observations and POC fluxes reported by .…”
Section: Comparison Of Export Fluxes To Previous Studiescontrasting
confidence: 38%
See 1 more Smart Citation
“…(2013) dataset may include more studies from diatom-rich ecosystems with high POC: 234 Th organic particles, such as observed by (Buesseler, 1998; not included in Le Moigne et al 2013), driving some of the discrepancy between our observations and POC fluxes reported by .…”
Section: Comparison Of Export Fluxes To Previous Studiescontrasting
confidence: 38%
“…There have been far fewer estimates of 234 Th-derived biomineral export fluxes Sanders et al, 2010;Le Moigne et al, 2012;Le Moigne et al, 2013). BSi and PIC fluxes observed during GB1 and GB2 are within the range previously observed during the Crozex study by the Crozet islands , the site of station GB2-27.…”
Section: Comparison Of Export Fluxes To Previous Studiesmentioning
confidence: 85%
“…3 in the North Atlantic Ocean) includes POC observations. Observed POC fluxes are from Dunne et al (2005), Gehlen et al (2006), andLe Moigne (2013). In these datasets, data have been obtained from sediment traps and/or 234 Th.…”
Section: Observationsmentioning
confidence: 99%
“…These data are a significant contribution to the rapidly growing global 234 Th data set (Le Moigne et al, 2013). In this work we describe the variability in upper ocean export fluxes and derive estimates of carbon export in the Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%